Faktor-Faktor Pembentuk Behavioral Intentions Pada Klub Persija Jakarta: Studi Penelitian Pada Komunitas Suporter The Jakmania - Rangga Lesmana; Santi Rimadias (STIE Indonesia Banking School, 2017)
In the times of growing football industry, behavioral intentions of football fans are also getting changed with the times. The behavior of the fans loyalty has become an important strategic tool used by the man-agement of football clubs in the country in the face of competition existing competition. The main objective of this study was to investigate the factors that form the behavioral intentions of supporters in a match watched his favorite football club. This research is classified as descriptive analysis method to take sam-ples and questionnaires as the main tool. Samples were supporters club Persija Jakarta, whice have a membership card The Jakmania, fans who live and stay in Jakarta and fans who've watched the match Persija Jakarta directly in the stadium. Respondents were selected using non probability sampling tech-niques and sampling purposive. The results of the analysis using Structural Equation Model (SEM) to ana-lyze the results. The results can be summarized as follows: 1. Sport attachment has positive influence on team identification, 2. Player attachment has positive effect on team identification, 3. Local city attachment has positive effect on team identification, 4. Fans community attachment did not effect on team identifica-tion, 5 . Team identification positive effect on behavioral intentions, 6. Game satisfaction positive effect on behavioral intentions, 7. Service satisfaction did not effect on behavioral intentions.